Transient active power control of HVDC links through impedance-based voltage angle comparison - Riebesel, David; Raab, Alexander; Porst, Johannis; Luther, Matthias; Heyde, Chris; Krebs, Rainer (2021 IEEE Madrid PowerTech, PowerTech 2021 - Conference Proceedings, 2021)
This paper provides a control approach for Voltage Source Converter (VSC) High-Voltage Direct Current (HVDC) systems based on data from Phasor Measurement Units (PMU) to improve transient stability during contingencies. Using graph theory and the shortest-path-problem, a strategy for PMU placement and for defining a control radius were carried out. The lowest electrical distance/impedance between the converters was identified to define the range of controllability of the HVDC and avoid loop flows. Further sensitivity analyses showed the importance of the input control signals. Based on the resulting area of controllability, a control scheme for a transient active power controller is introduced. It is shown that an impedance-based voltage angle control increases the stability of the power system during transients.
CRIS-Team Scopus Importer:2021-08-20
Keywords: active power control; HVDC; impedance-based controllability; PMU; transient stability; voltage angle